The Analysis of Understanding, Appreciation, and Satisfaction Levels of the People of Sikka Regency Regarding the Role of the Family Pastoral Commission in Supporting the First 1000 Days of Life - Yosefina Dhale Pora; Pasionista Vianitati; Teresia Elfi (Buletin Penelitian Kesehatan, 2025)
Background: Stunting prevention in Sikka Regency remains suboptimal, partly due to limited community awareness of the critical importance of the First 1,000 Days of Life. Faith-based organizations, such as the Family Pastoral Commission of the Maumere Diocese, have the potential to complement public health efforts through family-centered education; however, empirical evidence on community responses to these interventions is limited. This study aimed to examine the relationship between community understanding, appreciation, and satisfaction regarding the Commission’s role in supporting the First 1,000 Days of Life. Methods: A quantitative cross-sectional correlational study was conducted among 2,427 respondents from 38 parishes who had participated in First 1,000 Days of Life–related activities. Data were collected between June and September 2024 using validated questionnaires and analyzed using the Gamma correlation test. Results: Strong and statistically significant positive correlations were observed between understanding and appreciation (r = 0.973), understanding and satisfaction (r = 0.964), and appreciation and satisfaction (r = 0.931) (p < 0.05). Conclusion: Community understanding strongly influences appreciation and satisfaction toward faith-based interventions in stunting prevention. Strengthening educational content and facilitator capacity within family pastoral programs may enhance multisectoral efforts to reduce stunting.